Strategy to Use Local Government’s Facebook Page to Improve Public Services - ari cahaya puspitaningrum (Jurnal Sistem Informasi, 2019)
The population of internet users in Indonesia increase continuously form year to year along with the development of information technology infrastructure in Indonesia. This underlies the management of social media in the government agencies. The government sector could communicated with the citizens through social media such as Facebook as a form of direct communication to disseminate information for the citizens. Through current government social media accounts, it could be seen that the posting of official government Facebook account were still rare. Based on existing studies, it has not yet been reviewed the relationship of post and comment categorization on Facebook to improve the government's Facebook management strategy and public service improvement strategy. Therefore, this study was conducted so that the results could help the local government to maximize the management of Facebook accounts to be right on target, provide trustful information, and get a good response from the citizens. There were 30 Local Government Facebook accounts that have been analysed, resulting number of statuses and comment ranks in last 2 months. Then performing frequency analysis on 30-often-used words which will be used as a trigger to categorize. The results of the study are in the form of strategic suggestions for local governments to improve the content of each category through Facebook. Local governments are suggested to convey information from many aspects in a balanced manner in accordance with the needs of the citizens. Keywords– social media; categorization; strategy; local government